Fête champêtre des Jeunesses Socialistes du Nord. Au centre d.g.à.d.: 1.Ghesquière, 2.Delignies, 3.Cerezo
Fête champêtre des Jeunesses Socialistes du Nord. Au centre d.g.à.d.: 1.Ghesquière, 2.Delignies, 3.Cerezo.